The Philosopher as a Reader: A. Sverdiolas Reads G. Deleuze - Keršytė, Nijolė (Problemos, 2020)
Arūnas Sverdiolas’s way of reading Deleuze raises questions about the compatibility of two traditions: how and to what extent can a philosopher of Culture understand a philosopher of Nature and Life? Deleuze, formed in the rationalist tradition, resists the philosophy of Consciousness and Meaning, in which universality is held higher than empirical particularity. Abstract thinking – a cause of allergy for a Frenchman – is on the contrary an aspiration for a Lithuanian. Sverdiolas’s formation has its roots in resistance against Marxist-materialist thinking, with the help of philosophy of culture. He considers the whole philosophy of the 20th century as an anthropological philosophy of Culture. This does not facilitate understanding Deleuze’s thought. His vitalist philosophy is deemed paramaterialist and considered to be reductionist. Hence a contradiction: Deleuze is recognized as a gifted historian of philosophy, but his own thinking is viewed with scepticism, without seeing its roots in the history of philosophy. The reason why Deleuze’s philosophy rejects the anthropocentric perspective – that of the ego and of consciousness – is not considered.